2013
DOI: 10.1088/1367-2630/15/1/013007
|View full text |Cite
|
Sign up to set email alerts
|

A representation-free description of the Kasevich–Chu interferometer: a resolution of the redshift controversy

Abstract: Motivated by a recent claim by Müller et al (2010 Nature 463 926-9) that an atom interferometer can serve as an atom clock to measure the gravitational redshift with an unprecedented accuracy, we provide a representation-free description of the Kasevich-Chu interferometer based on operator algebra. We use this framework to show that the operator product determining the number of atoms at the exit ports of the interferometer is a c-number phase factor whose phase is the sum of only two phases: one is due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 56 publications
0
74
0
Order By: Relevance
“…, where Φ is the uniform Newtonian potential [29]. In this case, the resulting relativistic Hamiltonian is [26] …”
Section: Lorentz Violation In a Uniform Gravitational Fieldmentioning
confidence: 99%
“…, where Φ is the uniform Newtonian potential [29]. In this case, the resulting relativistic Hamiltonian is [26] …”
Section: Lorentz Violation In a Uniform Gravitational Fieldmentioning
confidence: 99%
“…In this Appendix we describe the population dynamics [30,31,33] of the two resonant atomic states driven by the Raman laser pulses. For this purpose we consider the interaction between a three-level atom and two laser pulses of the form…”
Section: A Raman Pulses: Superpositions and Exchangesmentioning
confidence: 99%
“…(37), during the time interval t i < t < t f , and with Ω j (t i ) = Ω j (t f ) = 0, is given by the evolution operator [33] …”
Section: A Raman Pulses: Superpositions and Exchangesmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar scenario was also studied in [11]. Both works also addressed the discussion about the interpretation of an experiment with atomic fountains [12], namely whether the Compton frequency can be associated with a physical clock in quantum interferometry [13][14][15][16][17], and showed that this cannot be the case as it would lead to an additional observable effect on the interferometric visibility. While the time dilation analysis used for massive particles does not directly apply to the propagation of light, the generalization of [1] to optical interferometry was studied in [2,18], where the Shapiro delay of a single photon can lead to a phase shift or loss of visibility in a quantum optical interferometer.…”
Section: Summary Of Related Studiesmentioning
confidence: 96%